ORIGINAL Programme: study background and design - Yu. A. Karpov (Кардиоваскулярная терапия и профилактика)
The paper presents the design of the ORIGINAL Programme (substituting indapamide generics with arifon retard in patients with arterial hypertension), evaluating blood pressure (BP) reduction in arterial hypertension (AH) patients starting the treatment with original indapamide retard and previously receiving mono- or combined therapy with indapamide generics, without adequate BP control. This prospective, multi-centre, open, noncomparative programme will involve 328 out-patient internists and cardiologists from 56 Russian cities. In total, 1372 patients will be treated and followed up for 3 months. The aim of the programme is to demonstrate the benefits of original indapamide, comparing to indapamide retard generics, in terms of BP control and safety.